2019
DOI: 10.7717/peerj.8277
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker potential of repetitive-element transcriptome in lung cancer

Abstract: Since repetitive elements (REs) account for nearly 53% of the human genome, profiling its transcription after an oncogenic change might help in the search for new biomarkers. Lung cancer was selected as target since it is the most frequent cause of cancer death. A bioinformatic workflow based on well-established bioinformatic tools (such as RepEnrich, RepBase, SAMTools, edgeR and DESeq2) has been developed to identify differentially expressed RNAs from REs. It was trained and tested with public RNA-seq data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Contrarily, HML7 and HML8 elements still remain poorly characterized. In particular, the only data regarding HML7 elements come from a recent study investigating the overall differential expression of repetitive elements in the transcriptome of patients with lung cancer for biomarker identification purposes [ 26 ]. In the study, participants were divided into patients who developed lung adenocarcinoma (LUAD) and patients who have developed small cell lung cancer (SCLC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, HML7 and HML8 elements still remain poorly characterized. In particular, the only data regarding HML7 elements come from a recent study investigating the overall differential expression of repetitive elements in the transcriptome of patients with lung cancer for biomarker identification purposes [ 26 ]. In the study, participants were divided into patients who developed lung adenocarcinoma (LUAD) and patients who have developed small cell lung cancer (SCLC).…”
Section: Introductionmentioning
confidence: 99%
“…In the study, participants were divided into patients who developed lung adenocarcinoma (LUAD) and patients who have developed small cell lung cancer (SCLC). The analysis showed a significant upregulation of the inner portion of HML-7 elements (known as HERVK11D-int) specific to LUAD but not found in SCLC patients [ 26 ]. Importantly, the study evaluated the whole group modulation, i.e., without any information about the individual HML7 member expression.…”
Section: Introductionmentioning
confidence: 99%
“…Families with a higher percentage of differentially expressed HERVs included HERV-H, HERV-K, and MER4. Interestingly, up-regulation of the HERV-H and HERV-K families has been proposed as novel diagnostic biomarkers [ 47 , 48 , 49 ], while the up-regulation of the MER4 family has been linked to progression-free survival (PFS) and overall survival (OS) [ 11 ]. MER4 HERVs have also been proposed as novel biomarkers for the response to immune checkpoint inhibitors (ICI), which, currently, are becoming the standard first-line treatment of advanced NSCLC for patients with high PD-L1 expression [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 On the other hand, many reports have indicated that HERVs are involved in different types of diseases. For example, HERV dysregulation has been detected in various types of cancer, such as breast cancer (BC), 17,18 melanoma, 19,20 kidney cancer, 21,22 lung cancer, 23,24 and ovarian cancer (OC). 25,26 In addition, HERVs are related to other diseases, such as type 1 diabetes, 27 neurological diseases 28 and other autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%